Language diversity as resource or as problem? Educator discourses and language policy at high schools in the Netherlands. Issue 2 (3rd April 2023) - Groff, Cynthia; Zwaanswijk, Wendy; Wilson, Ann; Saab, Nadira
ABSTRACT: The ways in which educators talk about diversity, and specifically about linguistic diversity, reflect underlying beliefs about language in society and influence teaching practice. Semi-structured interviews with 55 high school teachers in the Netherlands were analyzed qualitatively in order to identify teachers' discourse patterns related to the backgrounds and home languages of their students as well as language policies in the school context. The teachers struggle with the labels to categorize students with migration backgrounds, showing awareness of problematic insider-outsider labels. In terms of language diversity, deficit discourses about home languages and a monolingual focus on Dutch acquisition for immigrants highlights the prevalence of a language-as-problem orientation in decisions about language use. Language policy is focused on the development of skills in the target language, Dutch, and the promotion of a Dutch-only norm in the high schools. However, some interviewees describe the potential resource of the mother tongue in the classroom. Highlighting taken-for-granted assumptions in the discourses of Dutch teachers does not negate their best intentions in preparing their students for society. Rather it demonstrates the influence of language ideologies on teaching practice and the importance of teacher preparation and increased awareness of students' home language resources.